A Fatality Involving Furanylfentanyl and MMMP, with Presumptive Identification of Three MMMP Metabolites in Urine. Issue 4 (19th December 2018) - Nash, Christine; Butzbach, Danielle; Stockham, Peter; Scott, Timothy; Abroe, Greg; Painter, Ben; Gilbert, John; Kostakis, Chris
Abstract: The prevalence of new psychoactive substances (NPS) on the illicit drug market continues to grow, with new analogs being routinely synthesized. Routes of administration for these compounds are also diversifying, and recent research has shown an increase in the incorporation of NPS into vaping liquids. Among the most commonly encountered NPS are the cathinone and fentanyl analogs. Fentanyl analogs in particular have been implicated in a significant number of deaths, usually in combination with other prescription and illicit drugs. We report the case of a 44-year-old male with a history of polysubstance abuse found deceased at his home address. Items located within the vicinity of the deceased were found to contain furanylfentanyl and 2-methyl-4'-(methylthio)-2-morpholinopropiophenone (MMMP also known as MTMP, MMTMP, Irgacure 907 and Caccure 907). Both of these compounds were detected in the post-mortem peripheral blood of the deceased: furanylfentanyl at 1.6 ng/mL and MMMP at 6.7 ng/mL. MMMP is an unrestricted, commercially available photo-initiator used in the printing and polymer industry, which structurally can be classed as a highly modified cathinone. Although MMMP has been found previously in drug seizures, this is the first fatality in which MMMP has been detected. A number of other prescription and illicit drugs were also detected in the blood. MMMP was not detected in the post-mortem urine; however three metabolites, beta-hydroxy-MMMP, beta-hydroxy-MMMP-sulfoxide and beta-hydroxy-MMMP-sulfone, were presumptively identified. The significance of MMMP to the cause of death is uncertain as its pharmacological and toxicological profile is unclear.